Uso de métodos químicos para obtener polvos cerámicos del sistema (Sn, Ti)O2 - Ararat, C.; Varela, José Arana [UNESP]; Rodríguez-Páez, J. E. (Elsevier, 2005)
The (Sn,Ti)O2, system has a great interest due to its technological applications such as gas sensor and varistor. Although the thermodynamic properties and the kinetics of spinoidal decomposition in this system have been extensively studied, the general properties and applications of SnO2 - TiO2 binary compositions have been not investigated yet in depth. On the other hand, little work has been done to optimize the synthesis methods to obtain (Sn,Ti)O2 cerallmic powders, with pre - determinate physical and chemical characteristics. In this work the ceramic powders has been obtained by coprecipitation and polymeric precursor (Pechini) methods. The different physical chemistry phenomena that occurred during the synthesis were discussed. The (Sn,Ti)O2, ceramic powders were characterized with X- ray diffraction (XRD), thermal analysis (DTA/TG) and scanning electron microscopy (SEM). The knowledge about of steps and variables of synthesis process acquired with development of this work, we permited to obtain (Sn, Ti)O2, nanometers particles to low temperatures: to 450°C for coprecipitation method and to 600°C for Pechini method. The spinodal decomposition that ocurr to 900°C was discussed also.
Use of chemical methods to obtain (Sn, Ti)O2 ceramic powders
Keywords: (Sn,Ti)O2; Coprecipitation; Polymeric precursor; Synthesis